2016
DOI: 10.1093/mnras/stw2948
|View full text |Cite
|
Sign up to set email alerts
|

C60+– looking for the bucky-ball in interstellar space

Abstract: The laboratory gas phase spectrum recently published by Campbell et al. has reinvigorated attempts to confirm the presence of the C + 60 cation in the interstellar medium, thorough an analysis of the spectra of hot, reddened stars. This search is hindered by at least two issues that need to be addressed: (i) the wavelength range of interest is severely polluted by strong water-vapour lines coming from the Earth's atmosphere; (ii) one of the major bands attributed to C + 60 , at 9633Å, is blended with the stell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 19 publications
2
50
0
Order By: Relevance
“…Galazutdinov et al (2017) were unable to confirm the presence of the weakest 3 features in a sample of 19 heavily reddened Galactic sightlines observed from the ground. Instead of a constant ratio for the two strongest C 60 + DIBs (λ9577 and λ9632), as expected for electronic transitions arising from a A u 2 1 ground vibronic state, Galazutdinov et al (2017) found that the interstellar band ratio was highly variable among different lines of sight. We note, however, that if the observed transitions involve lower levels above the ground state (such as the split levels arising from Jahn-Teller distortion), a variable ratio could potentially occur.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Galazutdinov et al (2017) were unable to confirm the presence of the weakest 3 features in a sample of 19 heavily reddened Galactic sightlines observed from the ground. Instead of a constant ratio for the two strongest C 60 + DIBs (λ9577 and λ9632), as expected for electronic transitions arising from a A u 2 1 ground vibronic state, Galazutdinov et al (2017) found that the interstellar band ratio was highly variable among different lines of sight. We note, however, that if the observed transitions involve lower levels above the ground state (such as the split levels arising from Jahn-Teller distortion), a variable ratio could potentially occur.…”
Section: Introductionmentioning
confidence: 89%
“…Based on the laboratory measurements, five absorption features are expected (at 9348.4, 9365.2, 9427.8, 9577.0, and 9632.1 Å, with strength ratios 0.07:0.2:0.3:1.0:0.8; Campbell et al 2016b). Galazutdinov et al (2017) were unable to confirm the presence of the weakest 3 features in a sample of 19 heavily reddened Galactic sightlines observed from the ground. Instead of a constant ratio for the two strongest C 60 + DIBs (λ9577 and λ9632), as expected for electronic transitions arising from a A u 2 1 ground vibronic state, Galazutdinov et al (2017) found that the interstellar band ratio was highly variable among different lines of sight.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…While a number of such small molecules have been considered over the years, most detailed comparisons between laboratory and astronomical spectra have not yielded adequate matches (e.g., Tulej et al 1998;Motylewski et al 2000;Lakin et al 2000;McCall et al 2001;Guthe et al 2001;Salama et al 2011). Some five near-IR DIBs were recently attributed to the fullerene cation C 60 + Walker et al 2015; though see Galazutdinov et al 2017). Along with laboratory work, correlation studies have been performed to investigate the nature of carriers of the DIBs, by comparing DIB equivalent widths (EWs) with different interstellar parameters such as E B-V, the column densities of interstellar species (N(X)), and the strengths of other DIBs (e.g.…”
Section: Introductionmentioning
confidence: 99%